The relationship between ASEAN currencies with renminbi - Chong, Mui Foon. (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study aimed to examine the possibility of the Chinese Renminbi to be the common currency for the ASEAN region. For this purpose, this study inspected whether the Chinese Renminbi has a cointegrating relationship with each of the ASEAN currencies. In addition, this study also explored the causal impacts between the Chinese Renminbi and the ASEAN currencies.